2014
DOI: 10.1002/hep.27089
|View full text |Cite
|
Sign up to set email alerts
|

Systemic protection through remote ischemic preconditioning is spread by platelet-dependent signaling in mice

Abstract: Remote ischemic preconditioning (RIPC), the repetitive transient mechanical obstruction of vessels at a limb remote to the operative site, is a novel strategy to mitigate distant organ injury associated with surgery. In the clinic, RIPC has demonstrated efficacy in protecting various organs against ischemia reperfusion (IR), but a common mechanism underlying the systemic protection has not been identified. Here, we reasoned that protection may rely on adaptive physiological reponses toward local stress, as is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 37 publications
(86 reference statements)
2
48
1
Order By: Relevance
“…For ischemia/ reperfusion (I/R) experiments, 68% hepatic ischemia was induced as described. 22 Animals were sacrificed 6 hours after reperfusion, a time point that well reflects injury levels at later reperfusion times. 22 Hepatectomies (68% for normal liver regeneration, 86% for inducing liver failure) were performed as reported.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…For ischemia/ reperfusion (I/R) experiments, 68% hepatic ischemia was induced as described. 22 Animals were sacrificed 6 hours after reperfusion, a time point that well reflects injury levels at later reperfusion times. 22 Hepatectomies (68% for normal liver regeneration, 86% for inducing liver failure) were performed as reported.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…22 Animals were sacrificed 6 hours after reperfusion, a time point that well reflects injury levels at later reperfusion times. 22 Hepatectomies (68% for normal liver regeneration, 86% for inducing liver failure) were performed as reported. 23 Omegaven (parenteral fish oil emulsion; Fresenius Kabi AG, Oberdorf, Switzerland), was intravenously (i.v.)…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Brief episodes of ischemia with intermittent reperfusion are introduced at, for example, a limb, leading to systemic protection against subsequent insults as evinced on kidney, heart, liver, and other tissues. 17 We have recently identified a general mechanism that underlies the systemic protection conferred through RIPC 18 ; remote blood occlusion leads to serotonin release from platelets, which stimulates endothelial Vegf secretion to upregulate in target organs Il10 and Mmp8, acting in concert for protection. Interrupting this serotonin-Vegf-Il10/Mmp8 axis at any point renders RIPC inefficient in protecting against hepatic IR.…”
mentioning
confidence: 99%
“…Interrupting this serotonin-Vegf-Il10/Mmp8 axis at any point renders RIPC inefficient in protecting against hepatic IR. 18 Whether RIPC can likewise protect old liver is unclear. However, we have shown that Vegf administration is able to restore the diminished regenerative capacity of old liver to levels seen in young animals.…”
mentioning
confidence: 99%